2009
DOI: 10.2353/ajpath.2009.090171
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Permeability and Pathological Angiogenesis in Caveolin-1-Null Mice

Abstract: Caveolin-1, the signature protein of endothelial cell caveolae, has many important functions in vascular cells. Caveolae are thought to be the transcellular pathway by which plasma proteins cross normal capillary endothelium, but, unexpectedly, cav-1 ؊/؊ mice, which lack caveolae, have increased permeability to plasma albumin. The acute increase in vascular permeability induced by agents such as vascular endothelial growth factor (VEGF)-A occurs through venules, not capillaries, and particularly through the ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 59 publications
3
69
3
Order By: Relevance
“…By in vitro, ex vivo, and in vivo experiments, our results further confirm previous studies showing that the individual loss of eNOS 36 or caveolin-1 20,22 impairs the angiogenic response elicited by B16 melanoma cells inoculated in vivo. In addition, we show for the first time that reduced tumor angiogenesis in caveolin-1-null mice is due to unabated endothelial nitric oxide production, as genetic disruption of eNOS in the caveolin-1-null background partially or totally restores angiogenesis quantitatively.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…By in vitro, ex vivo, and in vivo experiments, our results further confirm previous studies showing that the individual loss of eNOS 36 or caveolin-1 20,22 impairs the angiogenic response elicited by B16 melanoma cells inoculated in vivo. In addition, we show for the first time that reduced tumor angiogenesis in caveolin-1-null mice is due to unabated endothelial nitric oxide production, as genetic disruption of eNOS in the caveolin-1-null background partially or totally restores angiogenesis quantitatively.…”
Section: Discussionsupporting
confidence: 80%
“…21 Defective mobilization of endothelial progenitors in response to ischemia was further documented in caveolin-1-deficient mice. 38 However, using tumor angiogenesis assays, both an increase 18,19 and a decrease 20,22 in the number of angiogenic blood vessels have been reported. Studies reporting increased tumor angiogenesis also documented increased tumor growth in caveolin-1-null mice, 18,19 whereas studies reporting decreased angiogenesis showed decreased tumor growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The established Cav-1 knockout mouse line has confirmed the importance of Cav-1 for the formation of morphologically distinct caveolae [9,10] . In addition, Cav-1 is also involved in the maintenance of cellular cholesterol homeostasis and lipid transport.…”
Section: Introductionmentioning
confidence: 88%